2018
DOI: 10.3390/ijms19072054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Tumor Growth Inhibition by Depletion of γ-Glutamylcyclotransferase (GGCT): A Novel Molecular Target for Anticancer Therapy

Abstract: γ-Glutamylcyclotransferase (GGCT), which is one of the major enzymes involved in glutathione metabolism, is upregulated in a wide range of cancers—glioma, breast, lung, esophageal, gastric, colorectal, urinary bladder, prostate, cervical, ovarian cancers and osteosarcoma—and promotes cancer progression; its depletion leads to the suppression of proliferation, invasion, and migration of cancer cells. It has been demonstrated that the suppression or inhibition of GGCT has an antitumor effect in cancer-bearing xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…The disruption of GGCT in HCT-116 cells markedly decreased the EMT associated markers and changed the morphology of GGCT-knockdown HCT-116 cells from mesenchymal-like cell type to the epithelial cell type, compared with the control cells. Disrupting GGCT was also observed to notably decrease the cell migration and invasion of HCT-116 cells, which was consistent with previous reports that indicated that GGCT influenced the migration and invasion of cancer cells ( 5 , 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…The disruption of GGCT in HCT-116 cells markedly decreased the EMT associated markers and changed the morphology of GGCT-knockdown HCT-116 cells from mesenchymal-like cell type to the epithelial cell type, compared with the control cells. Disrupting GGCT was also observed to notably decrease the cell migration and invasion of HCT-116 cells, which was consistent with previous reports that indicated that GGCT influenced the migration and invasion of cancer cells ( 5 , 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…GSH is a tripeptide consisting of glutamate, cysteine, and glycine, and its biosynthesis cycle requires γ-glutamylcyclotransferase, 5-oxoprolinase, glutamate cysteine ligase, and glutathione synthase [ 22 ]. Because mitochondrial GSH has a central role in ROS regulation, the depletion of GSH may be relevant to the development of steatohepatitis and NASH [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…PFKFB1 can be used as a potential molecular target for thyroid biotherapy. The GGCT play a role in cell proliferation, and the expression of this gene is a potential marker for cancer [57] .…”
Section: Discussionmentioning
confidence: 99%